Phase behavior and material properties of hollow nanoparticles - Schwarz, Ulrich S.; Safran, Samuel (Arxiv, 2000)
Effective pair potentials for hollow nanoparticles like the ones made from carbon (fullerenes) or metal dichalcogenides (inorganic fullerenes) consist of a hard core repulsion and a deep, but short-ranged, van der Waals attraction. We investigate them for single- and multi-walled nanoparticles and show that in both cases, in the limit of large radii the interaction range scales inversely with the radius, $R$, while the well depth scales linearly with $R$. We predict the values of the radius $R$ and the wall thickness